1995
DOI: 10.1104/pp.107.3.873
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll a/b-Binding Proteins, Pigment Conversions, and Early Light-Induced Proteins in a Chlorophyll b-less Barley Mutant

Abstract: The vast majority of the photosynthetic pigments in plants do not take part in the actual charge separation of the photosynthetic light reaction. Instead they function as antenna molecules that absorb photons and transfer, via other pigment molecules in the antenna, the absorbed energy to the RCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0
3

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(100 citation statements)
references
References 39 publications
7
90
0
3
Order By: Relevance
“…2A), drastically reduced amount of Lhcb1 (Fig. 2B) and the lack of immunodetectable Lhcb4, and Lhcb6 polypeptides (Bossmann et al, 1997;Krol et al, 1995Krol et al, , 1999. It is also demonstrated that the content of all individual carotenoid pigments in F2 mutant chloroplasts is strongly reduced as compared to the WT (Table 1).…”
Section: Consistent With Previous Reports the Quantitative Analysis Omentioning
confidence: 87%
See 2 more Smart Citations
“…2A), drastically reduced amount of Lhcb1 (Fig. 2B) and the lack of immunodetectable Lhcb4, and Lhcb6 polypeptides (Bossmann et al, 1997;Krol et al, 1995Krol et al, , 1999. It is also demonstrated that the content of all individual carotenoid pigments in F2 mutant chloroplasts is strongly reduced as compared to the WT (Table 1).…”
Section: Consistent With Previous Reports the Quantitative Analysis Omentioning
confidence: 87%
“…As the regulated ∆pH-and zeaxanthin-dependent NPQ is believed to occur within the LHCII antenna and depend on its oligomerization state (Horton et al 1996;Wentworth et al, 2004) the strongly reduced abundance of Lhcb proteins in the F2 mutant ( Fig. 1) (Bossmann et al, 1997;Krol et al, 1995Krol et al, , 1999 can easily explain the lower NPQ in the F2 mutant. In addition, an earlier study has demonstrated that the remaining LHCII proteins in Chlorina F2 mutant do not form trimers (Allen and Staehelin, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent works on in vitro reconstitution of Lhcb proteins indicated that Lhcb proteins can retain their native structure with aberrant Chl a : b ratios in vitro (Sandon et al, 1998). These results are apparently not consistent with the observation in many Chl-b de®cient mutants lacking most of the Lhc proteins, except for Lhcb5 (Harrison and Melis, 1992;Bossman et al, 1997;Kro  l et al, 1995). A mechanism involving Lhc-speci®c proteases (Lindahl et al, 1995;Yang et al, 1998) and/or a vesiclemediating transport system of Lhcb proteins (Hoober and Eggink, 1999) Genetic modi®cation of the antenna size might be a useful tool for future improvement in crop productivity.…”
Section: Chl B Biosynthesis Regulates Accumulation Of Lhcii and Antenmentioning
confidence: 90%
“…The enzymic reaction is light independent and occurs at the stromal side of the thylakoids using the substrates Zea or Anth, which are localized within the thylakoid membrane either in the lipid bilayer adjacent to (enzymic) proteins [12] or in pigment protein complexes, e.g. the inner antenna complexes [35] or the LHCs of PSI and II [36] or in ELIPs (early lightinduced proteins) [37]. The co-substrates of the reaction were reported to be NAD(P)H and 02 [16][17][18].…”
Section: Discussionmentioning
confidence: 99%